The costs and benefits of nurse migration on families: A Lesotho experience - Matsola E. Ntlale; Sinegugu E. Duma (AOSIS, 2012)
The present day migration of nurses from developing countries, to more developed countries,depletes these countries of this vital human resource, which is necessary to provide optimum quality nursing care to their populations. If nurse migration persists, the health systems of these countries face collapse. It is important that a nurse understands the costs and benefits of migration to their families, whom they leave behind. This is not only to curb the problems that may occur, but to help the migrant nurses to realise how migration affects their families, especially their children and spouses, before they decide to leave their home countries to work in foreign lands. The purpose of this study, which was exploratory, descriptive and qualitative, was to investigate and describe the experiences of family members, of migrant nurses, from the Maseru district of Lesotho, about the costs and benefits of nurse migration. The objectives were to explore and describe the disadvantageous costs and the benefits gained by the families of migrant nurses. These were explored through the research question 'What are the experiences of family members of migrating nurses with regard to the costs and benefits of nurse migration?' The target population of the study was families of migrant nurses from Lesotho. Using purposive sampling the families of two migrant nurses, who were colleagues of the researcher, were identified and approached to participate in the study. Snowball sampling was next utilised to recruit the remainder of the participants. In total, six families were identified and included in the study. The semi-structured interviews and field notes were the two data collection methods that were implemented. The Giorgi's (1970) steps for data analysis, as outlined in (Burns & Grove 2001:610), were followed and seven themes were discovered as findings. The themes that relate to the costs of nurse migration are: emotional instability, weaker family connections and increased responsibility. The themes that relate to the benefits of nurse migration for their families are: better household income, improved quality of life, essential skills development and travelling opportunities. The use of communication technology is recommended to increase contact across borders in order to reduce the emotional costs of nurse migration on the families of migrant nurses. The article provides a balanced view of the costs and benefits of nurse migration on their families.